Differences in Allometric Relationship of Two Dominant Woody Species Among Various Terrains in a Desert Region of Central Asia - Wu, Xue; Zheng, Xin-Jun; Mu, Xiao-Han; Li, Yan (Frontiers in Plant Science, 2021)
The allometric relationship among different functional traits is an ecological strategy for plants to promote resource utilization, which indicates the ability of plants to adapt to environmental changes coordinately. In this study, we conducted a field survey on Haloxylon ammodendron and H. persicum among different terrains (dune crest, eastern slope, western slope and inter-dune) in the Gurbantunggut Desert, obtained their quantitative and morphological characteristics, and analyzed their allometric relationships between plant height and canopy radius, plant height and basal diameter by using standardized major axis estimation. We found that: (1) The dominated terrains of H. ammodendron and H. persicum were different; (2) The individual morphology of the two Haloxylon species changed significantly with the terrains (p < 0.05), with the largest and smallest ones growing on the eastern slope and the inter-dune lowland, respectively; (3) Fixed allometric patterns were observed in the above-ground part of the two Haloxylon species, as the growth of canopy and basal stem was preferentially to plant height; (4) These allometric relationships were significantly affected by the terrain, and exhibited discrepancy between two species, they both invested less in plant height in windy habitats, such as the dune crest and western slope, but H. ammodendron growing on the western slope and H. persicum growing on the eastern slope invested more in basal diameter for strengthening mechanical support and resources acquisition, respectively. These results indicated that both studied species adopted an ecological strategy that allocating more resources to horizontal expansion rather than vertical growth, the terrain has an important influence on the allometric relationship of their above-ground parts, and the trade-off mechanism of main components investing was different for these two species due to habitat heterogeneity and ecological adaptability.